Methods for testing the quality of lightweight cellular concrete during pouring. (10th January 2022) - Liu, Xin; Qian, Xiaoxu; Pu, Shikun; Sheng, Ke; Sun, Dongning; Hong, Baoning
Highlights: The device and method for testing the surface strength of LCC on-site are developed. The device and method for testing the strength along the depth of LCC are developed. Reasonable pouring interval and suitable depth for pouring are determined. Abstract: Lightweight cellular concrete (LCC) has been widely used as a subgrade filling. The quality test of LCC during the pouring impacts the construction quality control and saves time, while few studies have been conducted on it. This study proposed the surface strength and strength along the depth of LCC in situ test devices and methods. Based on a practical engineering case in Guangdong Province, the quantitative measurement pouring interval between layers and the reasonable pouring thickness of a single layer was determined by the proposed measuring devices and methods.